The Oncology Data Network (ODN): A Collaborative European Data‐Sharing Platform to Inform Cancer Care. (5th September 2019) - Kerr, David; Arnold, Dirk; Blay, Jean‐Yves; Buske, Christian; Carrato, Alfredo; Gerritsen, Winald; Peeters, Marc
Abstract : The rise of precision oncology has made clinical decision making more complex than ever before. The Oncology Data Network was established to enable the clinical community to efficiently access potentially practice‐changing insights from an extended network of cancer centers. This article describes the progress to date and calls for greater collaboration.